DOI: 10.33915/etd.4286
|View full text |Cite
|
Sign up to set email alerts
|

Saudi English as a foreign language learners' attitudes toward computer -assisted language learning

Abstract: This study investigated Saudi English as a Foreign Language (EFL) Learners' attitudes toward Computer-Assisted Language Learning (CALL) at the Institute of Public Administration (IPA) in Saudi Arabia. Five research questions were developed: (1) What are the Saudi EFL learners' general attitudes toward CALL at the IPA? (2) What are Saudi EFL learners' attitudes toward the CALL software used at the IPA? (3) What are the differences between IPA Saudi EFL learners' attitudes toward CALL based on their years of Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
4
8
0
Order By: Relevance
“…The findings of the current study also concur with the study of Bulut and AbuSeileek ( 2007 ), who demonstrated the positive ideas and reactions toward the general use of CALL in learning English of 112 Saudi university students of English at King Saud University. Similarly, the findings of Al Shammari ( 2007 ) support the results of the present study. He proved that Saudi EFL students positively support the use of CALL software as an effective technique to develop the process of learning English.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings of the current study also concur with the study of Bulut and AbuSeileek ( 2007 ), who demonstrated the positive ideas and reactions toward the general use of CALL in learning English of 112 Saudi university students of English at King Saud University. Similarly, the findings of Al Shammari ( 2007 ) support the results of the present study. He proved that Saudi EFL students positively support the use of CALL software as an effective technique to develop the process of learning English.…”
Section: Discussionsupporting
confidence: 92%
“…Female subjects showed more positive and stronger overall attitudes toward the use of computer technology in the process of learning English than the male subjects. These findings are similar to those of Al Shammari ( 2007 ), who pointed out that gender had an important role in influencing the attitudes of the subjects. Specifically, the present study revealed that female participants proved more positive attitudes than male participants toward CALL software use in learning English.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The use of this new technology, has introduced an innovative scenario to the traditional instruction which resulted in positive perceptions towards Edmodo and MALL since it facilitates collaborative learning and students' self-confidence (Bozanta &Mardikyan, 2017;Yunkul & Cankaya, 2017). It also increases effectiveness of communication and language learning (Al-Said, 2015; Al- Shammari, 2007;Mokhta & Dzakiria, 2015;Sandu, 2015;Thongmak, 2013). Moreover, it is stated that implementation of Edmodo projects had a positive effect on students' motivation towards language learning in general (Alshawil & Alhomoud, 2016;Hariri & Bahanshal, 2015), and writing skill in particular (Tsiakyroudi, 2018) as it increased students' participation and engagement in the writing tasks.…”
Section: Students' Perceptions Of Edmodomentioning
confidence: 99%